Tradisi Pembacaan Surat Yasin : (Studi Living Qur’an di Pondok Pesantren Tahfidhul Qur’an Al-Hikmah Purwoasri Kediri) - Muhammad Halif Asyroful Bahana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This article aims to find out how the practice of reading Yasin's letter and explaining the reception of reading Yasin's letter to the lives of students at the Tahfidhul Qur'an Islamic Boarding School Al-Hikmah Purwoari. In their daily life, the students are required to take part in reading Yasin's letter after the Maghrib prayer in congregation. There are two focuses of study in this study, namely: First, the implementation of the tradition of reading Yasin's letter which is carried out after maghrib prayers. The second is regarding the reception of the tradition of reading Yasin's letter at the Tahfidhul Qur'an Islamic Boarding School Al-Hikmah Purwoari. This research is a field research and studied using qualitative research methods. Data collection was obtained through interviews, observation, and documentation. The data sources of this study were caregivers, students and alumni of the Tahfidhul Qur'an Islamic Boarding School Al-Hikmah Purwoasri Kediri. The results of this study indicate; First, the implementation of the tradition of reading Yasin's letter by following several procedures and implementations. Among them are reading tawassul and tahlil, reading Yasin's letter together, and praying. Second, the reception of the tradition of reading Yasin's letters which have objective, expressive, and documentary meanings. As with these activities, we get blessings from reading the Qur'an, our sins are forgiven by Allah SWT, we get the reward of 10 times reading the Qur'an and get peace of mind.